Morphology and distribution of species of the family Cucurbitaceae in Akwa Ibom State, Nigeria - Umoh, Omodot Timothy; Bassey, Margaret Emmanuel (Phytotaxa, 2021)
A study of the family Cucurbitaceae in Akwa Ibom State, Nigeria, was carried out in 15 Local Government Areas in different ecological zones across the State, where collections were made between May 2017 and June 2018. A total of eleven species in nine genera were collected: Citrullus lanatus, Citrullus mucosospermus, Cucumis sativus, Cucurbita maxima, Lagenaria siceraria, Lagenaria sphaerica, Luffa aegyptiaca, Momordica charantia, Siraitia africana, Telfairia occidentalis, and Trichosanthes cucumerina. Variation in morphology were seen in the investigated species in the stem shape that were cylindrical or angular, the compound or simple types of leaves, the indumentum of the leaf, the acute or acuminate leaf apices, the yellow or white petals, the cylindrical, spherical or irregular fruit shape, the lanceolate or irregular seed shape, and the pubescent or smooth seed. Cultivated cucurbits collected were 65% of the species investigated, while 35% occurred in the wild. A survey of the Cucurbitaceae collections in the Forest Herbarium Ibadan showed only four species recorded for Akwa Ibom State, of which only Luffa aegyptica was identified and collected in the course of this work. More cultivation should be encouraged, as this will serve as a conservation measure for cucurbits in the State.